Synthesis, Characterization and Electrochemical Properties of ?-Oxalato Copper(II) and Nickel(II) Complexes of Anthranilic Acid Schiff Base Ligands - Ali Saghatforoush, Lotf; Khalilnezhad, Raana; Ershad, Sohrab; Ghammamy, Shahriar; Hasanzadeh, Mohammad (Asian Journal of Chemistry, 2010)
Three copper(II) and three nickel(II) dinuclear oxalate-bridged compounds: [Cu(antrasal)2ox] (1), [Cu(antrathio)2ox] (2), [Cu(antrafur)2ox] (3), [Ni(antrasal)2ox] (4), [Ni(antrathio)2ox] (5) and [Ni(antrafur)2ox] (6) were prepared [antrasalH, antrathioH and antrafurH is the Schiff base formed by the condensation of anthranilic acid and salicylaldehyde, thiophene-2-carbaldehyde and furfural, respectively, ox = oxalate]. The oxalate-bridged binuclear metal complexes have been characterized by UV-Vis, IR and 1H NMR spectra and elemental analysis. The electrochemical behaviour of metal(II) complexes with Schiff-base ligands has been investigated by cyclic voltammetry and chronoamperometry techniques. The obtained results allow to assign anodic peaks at 1.1, 1.719 and 1.258 V to oxidation of Cu(II) to Cu(III) for: [Cu(antrasal)2ox], [Cu(antrathio)2ox and [Cu(antrafur)2ox], respectively and peaks at 1.125, 0.983 and 1.208 V to oxidation of Ni(II) to Ni(III) for [Ni(antrasal)2ox], [Ni(antrathio)2ox and [Ni(antrafur)2ox], respectively. Coefficient and diffusion coefficients were determined for these complexes. The obtained results of cyclic voltammetry and chronoamperometry showed that the total limitiy current of each of the studied compounds corresponds to one-electron transfer process.